The Processes of Consolidation and Effectiveness of Commercial Banks in the Years 2008-2013 - Gałecka, Agnieszka (Olsztyn Economic Journal, 2015)
The paper analyzes the mergers and acquisitions in the banking sector in Poland, and determined their impact on the structure of the sector and its effectiveness. The analysis was conducted between 2008 and 2013. In the analyzed sector was found growing concentration of capital in the form of mergers and acquisitions. All indications are that this trend will be maintained in subsequent years. Dominant share in the Polish banking sector are entities controlled by foreign investors, but in the period has been a slight decrease in this regard. In the analyzed period made as a result of mergers and acquisitions, we can observe an increase of concentration of the banking sector. In the period 2008-2013 there was a decrease in effectiveness of commercial banks; operation, which was caused by deteriorating macroeconomic situation. It can be said that the continuous consolidation processes in the period 2008-2013 have not influenced an improvement of financial results in the analysed sector, but the effects of these processes can be seen only in the long term.